2019
DOI: 10.1007/s12649-018-00570-0
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Food Waste: Variations of Physical–Chemical Characteristics and Consequences on Biomethane Potential

Abstract: Food waste (FW) storage influences its physical-chemical characteristics and anaerobic digestion (AD) performance. In this work we present the results of two weeks long experiment where two types of FW were stored in dedicated cells (10 L and 300 L). Air was evenly flushed on the top surface of the substrates and then analyzed to identify and quantify possible gaseous emissions. Solid and liquid fractions were also periodically sampled and analyzed for total solid, volatile solid, ammonia and VFA contents. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…During storage at the restaurant or supermarket site, the food waste undergoes rapid hydrolysis and acidification due to microbial activity as a batch-fermentation system under anaerobic conditions. 13 This will have a positive effect on subsequent anaerobic digester treatment. 14 The storage tank is periodically filled with food-waste slurry during the one-to two-week storage period.…”
Section: ■ Introductionmentioning
confidence: 99%
“…During storage at the restaurant or supermarket site, the food waste undergoes rapid hydrolysis and acidification due to microbial activity as a batch-fermentation system under anaerobic conditions. 13 This will have a positive effect on subsequent anaerobic digester treatment. 14 The storage tank is periodically filled with food-waste slurry during the one-to two-week storage period.…”
Section: ■ Introductionmentioning
confidence: 99%
“…performed a storage pretreatment under anoxic conditions, concluding that the best results in terms of stability were found with pretreatement periods of 5 and 7 days, with the methane yield ranging from 397 to 484 NmL CH 4 g −1 TVS added . This fact indicated that a storage time of around 1 week is an appropriate pretreatment before AD 33 …”
Section: Resultsmentioning
confidence: 97%
“…Additionally, at the end of the 7 days, an amount of leachate of 89 ± 9 mL was obtained, representing 22.4%, of the average mass sample of 394 ± 3 g. The generation of leachate for 4 and 7 days was similar, although there was an increase of around 15% from 4 days to 7 days. Degueurce et al 33 evaluated a storage pretreatment for OFMSW and observed that the conversion from solid to leachate ranged from 15 to 27% for different substrates after 2 weeks of storage, and the largest degraded portion (about 15%) occurred in the first 3 days. In addition, during a period of 5-8 days of storage and considering substrates of different compositions, the percentage of solid matter converted to leachate was 17.5%, 34 corroborating the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre-digester tank to store the feedstock collected and to feed the AD is required to buffer the irregularly collected volume of biowaste; however, the storage duration that may affect the AD performance and odor should be controlled [113]. Gonzalez et al [112] reported that a temperature increase of the feed to process conditions requires a significant amount of thermal energy, which strongly affects the efficiency of the process when operated at a low organic load.…”
Section: Observed Co-benefits and Limitationsmentioning
confidence: 99%